Retrospective review of lupus nephritis in a New Zealand multi-ethnic cohort. (July 2017) - Ly, E; Thein, H; Lam Po Tang, Michael
Increased lupus nephritis has been reported in Pacific Island and Maori populations. Previous studies suggest ethnic variation in response to immunosuppression treatment; however this has not been assessed in Pacific Island and Maori cohorts. This retrospective study reviewed class 3, 4 and 5 lupus nephritis outcomes and response to induction immunosuppression over a 10-year period in a New Zealand multi-ethnic cohort with high Pacific Island representation. This included 49 renal biopsies in 41 patients; by ethnicity Pacific Island 53.7%, Asian 31.7%, Caucasian 12.2%, and New Zealand Maori 2.4%. There were 11 class 3, 24 class 4 and 17 class 5 either alone or in combination with class 3/4. There were no statistically significant differences in renal function or proteinuria between ethnic groups at baseline. Pacific Island class 3/4 showed similar rates of renal remission with intravenous cyclophosphamide (6/8) and mycophenolate (4/7) induction treatment; results were comparable to the overall study group. There were no deaths or permanent dialysis requirements in the first six months of treatment, and no increased risk of adverse outcomes when stratified by ethnicity. Five lupus nephritis relapses occurred during maintenance treatment and there was no apparent ethnicity bias. Conclusion: Pacific Island people disproportionately present with increased lupus nephritis; and had comparable renal remission rates with intravenous cyclophosphamide and oral mycophenolate which were similar to the whole study cohort.